Orbital Emphysema as a Rare Complication of Retina Surgery. Issue 6 (November 2017) - Rodríguez-Cabrera, Lourdes; Rodríguez-Loaiza, José L.; Tovilla-Canales, José L.; Zuazo, Francisca
Abstract : Three patients with a history of previous pars-plana vitrectomy, 2 of them with perfluoropropane, and 1 with sulfur hexafluoride used, experienced eyelid swelling and pain after travelling to a higher altitude city. Gas was found in the orbit and periocular tissues, causing orbital compartment syndrome in 2 of the patients. The gas persisted on these patients despite surgical intervention, so hyperbaric oxygen therapy was advised. One patient refused, the other patient responded well to this therapy and the gas disappeared. The patient without an orbital compartment syndrome made a full recovery without needing medical or surgical intervention. Abstract : Intravitreal perfluoropropane and sulfur hexafluoride expansion due to high altitude travel can cause orbital emphysema with orbital compartment syndrome and vision loss.